Measuring the Quality of Services Provided in the Children’s Public Library Association from the Point of View of Parents - A Field Study in Lattakia City - محمد أسامة (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The study problem centered on the following two questions: What is the degree of quality of services provided in the General Children’s Library Association in Lattakia? What is the degree of parents’ satisfaction with it? The study aimed to present a picture of the reality of the quality of services provided in the General Children’s Association, and to show the degree of parents ’satisfaction with the quality of services provided at the General Children’s Association. A descriptive analytical approach was used. The study found a set of results, the most important of which are: There is a decrease in the quality of services provided in the Children’s Public Library Association from the point of view of parents of children and adolescents; there is a positive gap and medium satisfaction with the following quality dimensions: reliability, response, and safety, where the actual performance was greater from the expectations of the parents of children and adolescents; and there is a negative gap and dissatisfaction with the following dimensions of quality: tangibility and empathy, where the actual performance was less than the expectations of the parents of children and adolescents, and the parents of children and adolescents are interested in arranging the dimensions of the quality elements as follows: tangibility and safety in the first stage, Then the response and dependability in the second stage, and finally the empathy.